FACTORS AFFECTING THE ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT IN PAKEL TULUNGAGUNG DISTRICT - Prisda Novia Ananda; Novi Khoiriawati (State Islamic Institute (IAIN) Tulungagung, 2022)
Village fund management accountability as a form of accountability of the holder of the trust to the actions, performance, and decisions of the party giving the trust. With the existence of village funds, its management is required to use aspects of good governance where one of the pillars is accountability. So it is very important to know the factors that influence the accountability of village fund management in the village in Pakel District, Tulungagung Regency. This study aims to explain the influence of the role of village officials, community participation, and the use of information technology on the accountability of village fund management. The data of this study used a questionnaire or questionnaire which was distributed to 19 villages. Sampling using simple random sampling technique with a total sample of 114 respondents. And multiple linear regression analysis method is used to prove the research hypothesis. The results of this study indicate that (1) the role of village officials has a significant positive effect on village fund management accountability, (2) society participation does not inpact the accountability of the village fund management nt, (3) technology information utilizationhas a significant positive effect on the accountabilityof the village fund management, and (4) the role of village officials, the society participation, and the technology information utilizationhas a significant positive effect on the accountability of the village fund management.